Screening and management of the small for gestational age fetus in the UK: A survey of practice. (December 2018) - Sharp, A.; Duong, C.; Agarwal, U.; Alfirevic, Z.
Abstract: Background: Antenatal detection of the small for gestational (SGA) fetus has become an important indicator of quality of antenatal care in the UK. This has been driven by a desire to reduce stillbirth in this at risk group. Methods: We conducted a postal survey of 187 NHS consultant units within the UK to determine what the current practice for the detection and subsequent management of the suspected SGA fetus was following the guidance from the Royal College of Obstetricians and Gynaecologists (RCOG) in 2013. Results: The survey was performed in 3 rounds between 2016 and 2017 with a response rate of 65%. 85% of units assessed risk factors for SGA at booking. 81% of units used a customized symphysis fundal height (SFH) chart to screen for SGA with 95% of them using a cut off of <10th centile to refer for ultrasound assessment. When ultrasound is used to detect SGA, 80% of units used estimated fetal weight (EFW), with 89% of these using a cut off of <10th centile to diagnose SGA. Umbilical artery (UA) Doppler monitoring was undertaken in 97% of management and 94% delivered after 37 weeks. Only 24% of units had a dedicated fetal growth clinic, whilst 48% of units were able to offer computerised CTG to monitor the SGA fetus. Conclusions: Overall there is consistency in the screening methods for SGA (customised SFH charts) and identification of suspected SGA (SFH <10th centile, EFW <10th centile, UA monitoring and induction of labour at term). There was a low uptake of computerized CTG to monitor SGA babies and a low number of specialised fetal growth clinics.